Nazwy aptek w przestrzeni miejskiej Rzeszowa. Analiza semantyczna - Woś, Katarzyna (Słowo. Studia językoznawcze, 2012)
The article is devoted to a semantic analysis of pharmacies” names in the city of Rzeszów. The nomenclature of pharmacy falls into a category of chrematonyms that is named urbochrematonyms, ie. names which are inherent parts of the cityscape. The presence of pharmacies in the architecture of Polish cities has got a centuries-old tradition — the first pharmacies are dated to the second half of the 13** century. The analysis of over one hundred denominations - gathered through observation of Rzeszow streets, examination of a telephone directory, internet websites and a directory of pharmacies issued by the Regional Pharmaceutical Inspectorate — leads to distinguishing two tendencies: one, traditional, alluding to the form of emblem and names of the owners, and another, modern one, making use of acronyms. A characteristic feature is a large number of repeating names and lack of names related to the symbolism of nature.